Integrating general practitioners’ and patients’ perspectives in the development of a digital tool supporting primary care for older patients with multimorbidity: a focus group study - Schäfer, Ingmar; Jahns, Vivienne; Paucke, Valentina; Lühmann, Dagmar; Scherer, Martin; Nothacker, Julia (Frontiers in Digital Health, 2025)
IntroductionThe web application gp-multitool.de is based on the German clinical practice guideline “multimorbidity” and supports mutual prioritisation of treatments by GPs (general practitioners) and patients. The application facilitates sending hyperlinks to standardized assessments by email, which can be completed by patients on any suitable digital device. GPs can document clinical decisions. The tool also supports a structured medication review. Aims of this study were to consider needs and wants of the target groups in implementing the “multimorbidity” clinical practice guideline in a digital tool, and to examine themes of discussions in order to identify which aspects were considered most important for customising a digital tool.Materials and methodsWe conducted six focus groups with 32 GPs and six focus groups with 33 patients. Eight groups were conducted alongside the programming of the web application and four after finishing a prototype. GPs were recruited by mail and asked to invite up to six eligible patients from their practice to participate. Focus groups were based on semi-structured interview guides and discussed assessments, functionalities, usability and reliability of gp-multitool.de. Discussions were transcribed verbatim and analysed using content analysis.ResultsGPs wanted to avoid unnecessary and time-consuming functions and did not want to explore problems that they could not provide solutions for. For some assessments, GPs suggested simplifying scales or including residual categories. GPs and patients also addressed possible misunderstandings due to wording and discussed if some items might be too intimate or overtax patients intellectually. In most cases, participants confirmed usability, but they suggested changes in default settings and pointed out a few minor bugs that needed to be fixed. While some GPs considered data security an important topic, most patients were unconcerned with this issue and open to share their data.ConclusionOur study indicates that focus groups can be used to customize a digital tool according to the needs and wants of target groups and thus, improve content, functionality, usability, and reliability of digital tools. However, digital tools still need to be piloted and evaluated in everyday care. In our focus groups, study participants confirmed that gp-multitool.de can be a relevant approach for overcoming deficits in the information needed for mutual prioritisation of treatments by GPs and patients.